2021
DOI: 10.2147/cmar.s300897
|View full text |Cite
|
Sign up to set email alerts
|

A Serum Metabolomic Study Reveals Changes in Metabolites During the Treatment of Lung Cancer-Bearing Mice with Anlotinib

Abstract: Background Anlotinib is a vascular endothelial growth factor receptor tyrosine kinase inhibitor recommended for the treatment of advanced lung cancer patients after at least two previous systemic chemotherapies. Currently, many patients with lung cancer do not respond well to anlotinib treatment. Therefore, the aim of this metabolomic study was to determine the internal mechanism of anlotinib action at the molecular level and to identify the potential biomarkers and pathways associated with the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…We found that high-risk groups were more inclined to glyoxylate and dicarboxylate metropolis, pentose phase pathway, arginine and proline metropolis and other pathways. Among them, the metabolism of glyoxylic acid and dicarboxylic acid is the most important way for the lung cancer treatment drug erlotinib to regulate in vivo [40] . This pathway is highly related to TCA cycle, which is very important for the proliferation and apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that high-risk groups were more inclined to glyoxylate and dicarboxylate metropolis, pentose phase pathway, arginine and proline metropolis and other pathways. Among them, the metabolism of glyoxylic acid and dicarboxylic acid is the most important way for the lung cancer treatment drug erlotinib to regulate in vivo [40] . This pathway is highly related to TCA cycle, which is very important for the proliferation and apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al. ( 34 ) have recently published serum metabolomics in lung cancer-bearing mice after treatment with anlotinib. Compared with the control group, 13 differential metabolites and five potential metabolic pathways (i.e., glyoxylate and dicarboxylate metabolism; tryptophan metabolism; glycine, serine, and threonine metabolism; phenylalanine metabolism; and valine, leucine, and isoleucine biosynthesis) were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al demonstrated that using cell metabolomics, the AA metabolism regulation, HIF-1, and PI3K-Akt signalling pathways were highly related to osimertinib resistance [ 15 ]. All these research studies clearly state the importance and broad application of metabolomics to track the specific changes in LC metabolites in patients after the drug’s action [ 16 ].…”
Section: Importance Of Serum Metabolites Collected Before During and ...mentioning
confidence: 99%
“…Pan et al observed the anlotinib-regulated amino acids (AAs) metabolism (tryptophan, threonine, glycine, serine, phenylalanine) and AA biosynthesis (valine, leucine, isoleucine) pathways, and glyoxylate and decarboxylate pathways in vivo. These pathways are essential in cancer cell metabolism and are associated with the TCA cycle [ 16 ]. Tryptophan is a crucial AA for protein synthesis and a critical regulator in cancer progression [ 19 ].…”
Section: Importance Of Serum Metabolites Collected Before During and ...mentioning
confidence: 99%